Rights And Treatment Of Prisoners Of War Under Islamic International Humanitarian Law: A Legal Analysis - Abdullahi , Ibrahim (Archives of Business Research, 2019)
The central thrust of this paper is on the legal analysis of the rights and treatment of prisoners of war under Islamic International Humanitarian law. Islamic Law as a complete system of law has corresponding rules regulating the treatment of prisoners of war and imbibed therein is the elementary considerations of humanity. This paper makes use of the doctrinal methodology in making legal analysis of the Rights and Treatment of Prisoners of War under Islamic International Humanitarian and in so doing, making cross references with the International Humanitarian Laws of the Geneva Conventions. The paper concludes that the fundamental rules and principles relating to the rights of prisoners of war under Islamic Law show striking similarities with that of the Geneva Conventions. However, issues of maltreatment of persons detained in armed conflicts as well as lack of political will by belligerents to respect and prevent violation of International Humanitarian Law (IHL) are increasingly common area of concern to the extent that Islamic laws and norms relating to the rights and treatment of prisoners of war is a better alternative to conventional International Humanitarian Laws and can be used as a model for improving the contemporary International Legal Regime